EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) DITINJAU DARI KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK - Joko Sutrisno AB; Elvandri Yogi Pratama; Filardi Anindito (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2022)
This research is a quasi-experimental research. This study aims todetermine the effectiveness of the TGT (Teams Games Tournament) type ofcooperative learning model in terms of students' mathematical communicationskills using a posttest-only control-group design. The population in this study wereall students of class VIII SMP Tri Sukses Natar in the academic year 2021/2022.The sample in this study were students of class VIIIB and VIIIC determined bypurposive sampling technique. The data in this study are quantitative data onstudents' mathematical communication skills obtained through tests of students'mathematical communication skills with questions in the form of descriptions. Theresults obtained are the average mathematical communication ability in theexperimental class is 75.46, while in the experimental class is 63.43. Theachievement of indicators of students' mathematical communication skills in theexperimental class was 74.57%, while in the control class it was 62.65%. Based onthe results and discussion, it was concluded that the TGT type of cooperativelearning model was effective in terms of the mathematical communication skills ofeighth grade students of SMP Tri Sukses Natar in the odd semester of the 2021/2022academic year